Validity and Reliability of the Turkish Form of Technology-Rich Outcome-Focused Learning Environment Inventory - (:unkn) unknown (EDAM, 2011)
The purpose of the study was to investigate the reliability and validity of a Turkish adaptation of Technology-Rich Outcomes-Focused Learning Environment Inventory (TROFLEI) which was developed by Aldridge, Dorman, and Fraser. A sample of 985 students from 16 high schools (Grades 9-12) participated in the study. Translation process followed translation committee, back translation, and decentralizing methods by teacher educators. Once equivalency of the Turkish form was established, the construct validity of the scale was examined with exploratory factor analysis followed by the confirmatory factor analysis which tested the original scale model. Additionally, Cronbach alpha correlation coefficients, corrected item-total correlations, and t-tests between items' means of upper 27%-lower 27% points were calculated. In contrast to original 80 items scale. Turkish form of TROFLEI consisted of 77 items after 3 items were dropped. Exploratory and confirmatory factor analysis results supported the original 10 factor structure. The Cronbach alpha coefficients varied between 0.81 and 0.92. Corrected item-total correlations ranged from 0.33 to 0.67. According to t-test results, differences between each item's means of upper 27% and lower 27% points were significant. Goodness of fit indices of confirmatory factor analysis indicated a good fit between the original model and data ((sic)2 /sd=2,95, RMSEA=0.051, RMR=0.078, SRMR=0.056, CFI=0.97, TLI=0.97). The results of this research provide strong evidence of the sound psychometric properties of Turkish form of TROFLEI.
Keywords: Learning Environment; Technology-Rich Outcomes-Focused Learning Environment Inventory (TROFLEI) Scale Adaptation; FIT INDEXES; INSTRUMENT